2017
DOI: 10.18632/oncotarget.18992
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine-specific phospholipase C inhibition reduces HER2-overexpression, cell proliferation andin vivotumor growth in a highly tumorigenic ovarian cancer model

Abstract: Antagonizing the oncogenic effects of human epidermal growth factor receptor 2 (HER2) with current anti-HER2 agents has not yet yielded major progress in the treatment of advanced HER2-positive epithelial ovarian cancer (EOC). Using preclinical models to explore alternative molecular mechanisms affecting HER2 overexpression and oncogenicity may lead to new strategies for EOC patient treatment. We previously reported that phosphatidylcholine-specific phospholipase C (PC-PLC) exerts a pivotal role in regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…In a previous work on the same experimental model we reported that cisplatin induced cytostatic effects associated with a metabolic shift of cancer cells towards accumulation of MRS‐detected neutral lipids, whereas the tCho profile failed to be perturbed in either cultured cells or xenografts . On the other hand, the inhibition of PC‐plc by tricyclodecan‐9‐yl‐potassium xanthate induced a reduction of cell proliferation and in vivo tumor growth in SKOV3.ip xenografts . The tumor growth arrest was associated with an about 50% reduction of HER2 mRNA and protein expression levels, as well as with a drop in the intracellular PCho content in SKOV3.ip cells.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In a previous work on the same experimental model we reported that cisplatin induced cytostatic effects associated with a metabolic shift of cancer cells towards accumulation of MRS‐detected neutral lipids, whereas the tCho profile failed to be perturbed in either cultured cells or xenografts . On the other hand, the inhibition of PC‐plc by tricyclodecan‐9‐yl‐potassium xanthate induced a reduction of cell proliferation and in vivo tumor growth in SKOV3.ip xenografts . The tumor growth arrest was associated with an about 50% reduction of HER2 mRNA and protein expression levels, as well as with a drop in the intracellular PCho content in SKOV3.ip cells.…”
Section: Discussionmentioning
confidence: 93%
“…In vivo MRI technologies, including diffusion‐weighted MRI (DWI) and localized MRS, have been successfully applied by our group, shortly after the in vivo administration of either conventional or innovative drugs, for the identification of their induced functional changes and metabolic alterations in preclinical models, and even in the presence of tumor growth inhibition rather than tumor shrinkage . Clinical DWI applications also showed encouraging results in the imaging of a variety of gynecological cancer lesions …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition PC‐PLC activity was associated with progressive decreases of mesenchymal traits in breast cancer cells (Abalsamo et al, ). PC‐PLC inhibition could also reduce proliferation of epithelial ovarian cancer cells and in vivo tumor growth in a highly tumorigenic ovarian cancer model (Paris et al, ). In addition, inhibition PC‐PLC interferes with proliferation, invasion, and glycolysis in U87MG glioma cells (Mercurio et al, ).…”
Section: Introductionmentioning
confidence: 99%